Dispensability of the SAC Depends on the Time Window Required by Aurora B to Ensure Chromosome Biorientation. - Marta Muñoz-Barrera; Isabel Aguilar; Fernando Monje-Casas (PLoS ONE, 2015)
Aurora B and the spindle assembly checkpoint (SAC) collaborate to ensure the proper biorientation of chromosomes during mitosis. However, lack of Aurora B activity and inactivation of the SAC have a very different impact on chromosome segregation. This is most evident in Saccharomyces cerevisiae, since in this organism the lack of Aurora B is lethal and leads to severe aneuploidy problems, while the SAC is dispensable under normal growth conditions and mutants in this checkpoint do not show evident chromosome segregation defects. We demonstrate that the efficient repair of incorrect chromosome attachments by Aurora B during the initial stages of spindle assembly in budding yeast determines the lack of chromosome segregation defects in SAC mutants, and propose that the differential time window that Aurora B kinase requires to establish chromosome biorientation is the key factor that determines why some cells are more dependent on a functional SAC than others.